Impact of Environmental Noise and Sleep Health on Pediatric Hypertension Incidence: ABCD Study - Augusto César F. De Moraes; Martin Y. Ma; Marcus V. Nascimento‐Ferreira; Ethan H. Hunt; Deanna M. Hoelscher (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Pediatric hypertension is linked to environmental factors like neighborhood noise disrupting sleep, which is crucial for health. The specific interaction between noise and sleep health in causing hypertension still needs to be explored. Methods and Results We analyzed data from 3320 participants of the ABCD (Adolescent Brain Cognitive Development) study, recruited across 21 US cities and monitored from 2018 to 2020 through 2020 to 2022. Participants with complete data on Fitbit‐tracked sleep, blood pressure, height, neighborhood noise, and covariates (biological sex, race and ethnicity, pubertal stage, waist circumference) were included. Hypertension was defined as average blood pressure ≥95th percentile for age, sex, and height. Sleep health was categorized on the basis of daily duration: healthy (9–12 hours), moderately healthy (±1 hour from optimal), and low (≥1 hour deviation). Noise exposure was measured as median nighttime anthropogenic noise levels by zip code. The incidence of hypertension increased from 1.7% (95% CI, 1.4–2.1) in 2018 to 2020 to 2.9% (95% CI, 2.4–3.6) in 2020 to 2022. Adolescents with healthier sleep had a lower risk of developing hypertension (relative risk, 0.63 [95% CI, 0.25–0.82]), while no significant effects were found for neighborhood noise alone or in combination with sleep health. Conclusions Adequate sleep significantly reduces the risk of hypertension in adolescents, independent of environmental noise exposure. These findings underscore the importance of promoting good sleep hygiene among youth to mitigate hypertension risk.